В стране вечных каникул: повесть-сказка / А. Г. Алексин - Алексин Анатолий Георгиевич (Логосвос, 2016)
Экземпляры: БС (20161025) / Инвентарный номер: РТШ54447 / Цена: / Сис.шифр: Р2 / Авт.знак: А 48 / ГРНТИ: 17.82.93 / ББК: 84(2)